The role of the Bible in language standardization processes - Currie, Oliver (Jezik in slovstvo, 2022)
Bible translations have played a central role in language standardization processes, because the Bible’s unique authority as a text favoured the selection of the variety used in the Bible as a language standard and because the wider distribution the Bible enjoyed compared to other texts, in particular in Renais-sance and Reformation Europe, then facilitated the diffusion of a biblical language standard. This article examines of the role of the Bible in language standardization processes focusing on a historical case study of Welsh. The language of the first complete Welsh Bible translation in 1588 is widely recognised to have formed the basis of standard literary Welsh, yet there has to date not been a sys-tematic investigation of how the Welsh biblical standard developed or came to be adopted. The article reassesses the traditional, but unsubstantiated view that the language of the 1588 Bible translation was based on an existing medieval poetic literary standard and advances an alternative hypothesis that the biblical standard was essentially shaped by the process of revision of earlier translations, as the 1588 and ultimately canonical translation represented a reaction against the linguistic inconsistencies and idiosyncrasies of earlier translations of the New Testament and Psalms.
Keywords: Bible translation; codification; jezikovna standardizacija; kodifikacija; language standardization; prevajanje; sociolinguistic variation; sociolingvistična variantnost; Sveto pismo; valižanščina; Welsh